Evaluation of Drinking Water Treatment Plant Design at Badan Layanan Umum Daerah (BLUD) Drinking Water Treatment Plant - Shalahuddin Nur, Adila; Sururi, Mohamad Rangga; Ramadhan, Anugrah (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2025)
This study evaluated the performance of the BLUD Drinking Water Treatment Plant (WTP) in Cimahi to identify parameters exceeding national standards and assess design and operational adequacy. Raw water quality did not comply with PP No. 22/2021 for BOD (11.9 mg/L), COD (24.1 mg/L), detergent (0.426 mg/L), fecal coliform (4.27 × 10⁷ MPN/100 mL), total coliform (1.14 × 10⁶ MPN/100 mL), nitrite (0.093 mg/L), sulfate (0.328 mg/L), TSS (88 mg/L), and zinc (0.061 mg/L). Treated water failed Permenkes No. 2/2023 for color (22.5 TCU) and residual chlorine (0.16 mg/L), while negative removals were observed for fluoride, manganese, nitrite, TDS, and color. Evaluation revealed several design flaws: bar screen spacing of 25 mm and thickness of 10 mm (required 4–8 mm and 25–50 mm); coagulation with constant PAC dosing (18 mg/L) without jar testing; flocculation detention time of 22 min with constant velocity gradients (30.5 s⁻¹) instead of 30–45 min with decreasing gradients; sedimentation with detention time of 0.97 h and surface loading of 3.75 m³/m²·h (required 1.5–3 h and 3.8–7.5 m³/m²·h); filtration with backwash velocity of 41.86 m/h and duration of 5 min (required 46–50 m/h and 10–15 min); and disinfection with velocity gradient of 111 s⁻¹ (required 500 s⁻¹). Revised designs included reducing bar spacing to 8 mm and thickness to 50 mm, implementing routine jar testing, extending flocculation detention to 30.1 min with step-down gradients (34–26 s⁻¹), deepening sedimentation basins to 6 m (detention 1.54 h, surface loading 3.87 m³/m²·h), increasing backwash velocity to 46.56 m/h for 10 min, and installing a static mixer (G = 1427 s⁻¹) for chlorine application. These improvements are expected to enhance removal efficiency, eliminate negative removals, and ensure compliance with Indonesian drinking water standards.